Prevalence, Risk Factors, and Coinfection of Urogenital Schistosomiasis and Soil-Transmitted Helminthiasis among Primary School Children in Biase, Southern Nigeria - Kenneth Nnamdi Opara; Eteye Udobong Wilson; Clement Ameh Yaro; Luay Alkazmi; Nsima Ibanga Udoidung; Friday Maduka Chikezie; Bassey Eyibio Bassey; Gaber El-Saber Batiha (Journal of Parasitology Research)
Schistosomiasis and soil-transmitted helminthiasis (STH) are neglected tropical diseases (NTDs) that cause chronic infections and ill health. The study was carried out to determine the current infection status and risk factors associated with Schistosoma haematobium and soil-transmitted helminth (STH) coinfection among school children in Biase Local Government Area (LGA), Cross River State, Nigeria. A cross-sectional study was carried out. Urine and fecal samples were randomly collected from 630 school children in six villages of Biase LGA. Urine sedimentation and Kato-Katz techniques were used to diagnose urogenital schistosomiasis and STHs, respectively. A structured questionnaire was used to collect demographic information and risk factors. The prevalence of S. haematobium in Biase LGA was 6.03%, with males (27 pupils, 9.00%) significantly more (χ2=8.903, p value = 0.003, C.I.=−82.650–120.650) infected than the females (11 pupils, 3.33%), while the prevalence of STH infection was 11.27% with no significant difference (χ2=0.002, p value = 0.962, C.I.=−16.441–54.559) in prevalence between males (34 pupils, 11.33%) and females (37 pupils, 11.21%). Prevalence of S. haematobium and STHs ranged from 1.82 to 19.13% and from 4.55 to 19.05% within the communities, respectively, with Abini (22 pupils, 19.13%) and Adim (20 pupils, 19.05%) communities having the highest prevalence for S. haematobium and STHs, respectively. The most infected age group was 11–13 years (21 pupils, 9.68%) for S. haematobium and 14–16 years (5 pupils, 21.74%) for STHs. Ascaris lumbricoides, hookworms, and Trichuris trichiura had prevalence of 5.56%, 3.02%, and 2.70%, respectively. An overall prevalence of 7.14% and 8.41% was observed for haematuria and proteinuria, respectively. Prevalence of coinfection among the parasites was 4.76%. Male pupils (OR=2.868, C.I.: 1.397–5.889), pupils of the age group of 11–13 years (OR=2.496, C.I.: 1.287–4.838), school children that swim (OR=1.527, C.I.: 0.784–2.974), those that cross streams to farm (OR=25.286, C.I.: 4.091–156.283), those that visit stream or river severally (OR=3.077, C.I.: 1.204–7.863), and those whose home is 1 km (OR=3.116, C.I.: 1.292–7.518) from the stream are at higher odds of infection with S. haematobium. For STHs, male pupils (OR=1.012, C.I.: 0.617–1.659), pupils of the age group of 11–13 years (OR=2.609, C.I.: 1.582–4.302), pupils that walk barefoot (OR=18.746, C.I.: 6.786–51.783), those that do not wash fruits and vegetables before eating (OR=2.334, C.I.: 1.400–3.892), those that do not wash hands after using the toilet (OR=1.200, C.I.: 0.730–1.973), those that eat soils (OR=2.741, C.I.: 1.533–4.902), those that drink water from streams or rivers (OR=189.509, C.I.: 24.807–1447.740), and those that use pit latrine (OR=2.920, C.I.: 1.746–4.885) and/or open defecation (OR=2.552, C.I.: 1.454–4.479) are at high odds of being infected with STHs. Urogenital schistosomiasis and soil-transmitted helminthiasis are still endemic diseases in Biase LGA. Although the degree of infection is quite low or moderate, there is a need to intensify and sustain control measures such as provision of sustainable clean water supply, health education intervention, and chemotherapy.